2016
DOI: 10.2344/14-00008.1
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' and Parents' Attitude Toward Nitrous Oxide Use in Kuwait

Abstract: The aim of this study was to investigate the attitude of dentists in Kuwait toward the use of nitrous oxide sedation as a behavior management technique (BMT) for pediatric patients and assess their training in nitrous oxide sedation. In addition, we assessed parents' knowledge of and attitude toward the use of nitrous oxide as a BMT for their children. The objective was to determine if nitrous oxide sedation is being provided and utilized as a means to enhance dental care for pediatric patients. A cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Nitrous oxide sedation, which frequently reduces stress and anxiety in children undergoing dental treatment, is also commonly accepted by parents. 5 Hence, this systematic review and meta-analysis of randomized controlled trials aims to identify the level of sedation produced by a combination of nitrous oxide and parenteral midazolam in both adults and children.…”
mentioning
confidence: 99%
“…Nitrous oxide sedation, which frequently reduces stress and anxiety in children undergoing dental treatment, is also commonly accepted by parents. 5 Hence, this systematic review and meta-analysis of randomized controlled trials aims to identify the level of sedation produced by a combination of nitrous oxide and parenteral midazolam in both adults and children.…”
mentioning
confidence: 99%
“…Some previously reported surveys have also reported a high acceptance of NIOS. According to a survey in 2016, investigated the attitude of parents towards NIOS, and it was concluded that most parents in Kuwait are unaware of nitrous oxide sedation as a Behaviour Management Technique, but more than half of them accepted its usage for their children upon their dentist's advice and recommendation [16] . In 2018, an epidemiological questionare study was conducted on north Indian children of age group 2-5 years, parents or guardian (Himachal Pradesh) to find out the awareness, knowledge and attitude towards conscious sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Monisha et al [ 9 ] found that as few as 10% of dentists in Chennai, India provided sedation. The low level of use of sedation in dentistry has been largely attributed to a lack of proper training and proper sedation facilities and equipment, and the additional cost of purchasing equipment [ 8 10 11 ].…”
Section: Introductionmentioning
confidence: 99%